High-toughness ultra-fine grain magnesium-lithium alloy bar and preparation method thereof
Through vacuum casting-hot extrusion-lined pipe rotary forging process and combined with component design, the problem of difficult magnesium-lithium alloy to take into account high strength and good plasticity is solved, and the preparation of high-strength and tough ultrafine crystalline magnesium-lithium alloy rods is realized, with high strength and toughness and suitable for industrial production.
Patent Information
- Application Number
- CN202510266103.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-07
- Publication Date
- 2025-05-27
AI Technical Summary
Existing magnesium lithium alloys are difficult to take into account high strength and good plasticity, and the preparation process is complex and the raw material loss is high, making it difficult to be suitable for large-scale industrial production.
The vacuum casting-hot extrusion-lined pipe rotary forging process is adopted, combined with the component design, and high-strength ultrafine crystal magnesium-lithium alloy rods are prepared. This process achieves uniform component distribution and high strength and toughness of magnesium lithium alloy by strictly controlling the vacuum degree, smelting temperature and hot extrusion parameters.
It has achieved high strength and toughness of magnesium lithium alloy rods, tensile strength is not less than 330MPa, and elongation is not less than 20%. At the same time, the process flow is simplified, raw material loss is reduced, and it is suitable for large-scale industrial production.
Smart Images

Figure CN120041732A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of processing and manufacturing of high-performance ultra-light materials, and particularly relates to a high-strength and tough ultra-fine grain magnesium-lithium alloy bar and a preparation method thereof. Background Art
[0002] Magnesium-lithium alloy (Mg-Li alloy) is one of the lightest metallic structural materials at present, and its density is usually between 1.3 g / cm 3 ~1.6 g / cm 3 , far lower than that of aluminum alloy (2.7 g / cm 3 ). This ultra-light characteristic combined with certain mechanical properties will make it have important application value in the fields of aerospace and national defense. However, the strength of magnesium-lithium alloy generally focuses on about 280 MPa, rarely exceeding 320 MPa, and it is difficult to meet some application scenarios with higher requirements for the strength of structural materials.
[0003] The matrix phase of low-lithium magnesium-lithium alloy generally consists of α-Mg phase with a hexagonal close-packed structure. This series of alloys has fewer slip systems. Although this series of alloys can improve the strength of materials to a certain extent through deformation processes such as rolling and extrusion, the plasticity is often greatly reduced due to work hardening and precipitation strengthening. In order to obtain high-strength and tough magnesium-lithium alloy, preparing ultra-fine grain alloy materials through severe plastic deformation has become a better choice. However, severe plastic deformation processes, such as equal-channel angular pressing and accumulative roll-bonding technology, have complex preparation processes and high raw material losses, and are not suitable for large-scale industrial production.
[0004] Therefore, in order to be suitable for large-scale industrial production, it is necessary to shorten the process flow and reduce raw material losses in the process of preparing high-strength and tough ultra-fine grain magnesium-lithium alloy bars. Summary of the Invention
[0005] The technical problem to be solved by the present invention is to provide a preparation method of a high-strength and tough ultra-fine grain magnesium-lithium alloy bar aiming at the deficiencies of the above-mentioned existing technologies. Through the vacuum melting-casting - hot extrusion - lining tube rotary forging process and combined with composition design, this method improves the workability of magnesium-lithium alloy, and prepares a magnesium-lithium alloy bar with a smooth and flat surface, no obvious defects, uniform distribution of ultra-fine grains, and balanced strength and toughness. At the same time, the whole process flow is short and the loss is low, solving the problems that the existing magnesium-lithium alloy is difficult to balance strength and plasticity, and the preparation process is complex and the raw material loss is high.
[0006] To solve the above technical problem, the technical solution adopted by the present invention is: a preparation method of a high-strength and tough ultra-fine grain magnesium-lithium alloy bar, characterized in that the magnesium-lithium alloy bar is composed of the following components by mass percentage: Li 2% - 5%, Zn 6% - 8%, Y 1.5% - 3.5%, and the rest is magnesium and inevitable impurities. The preparation method includes the following steps:
[0007] Step 1, Vacuum induction melting: Turn on the circulating water and vacuum system of the vacuum induction melting furnace. When the vacuum degree is lower than 6×10 -2 Pa, turn off the vacuum system and introduce argon into the furnace. Heat up and keep warm for melting respectively, so that the magnesium ingot and lithium ingot are completely melted. Then gradually add zinc granules and magnesium-yttrium master alloy through the feeder. Turn on the mechanical stirring system to stir at a fixed speed. At the same time, heat up for melting to obtain the molten metal. After heating up and keeping warm, pour the molten metal into the mold. After cooling, a magnesium-lithium alloy ingot is obtained;
[0008] Step 2, Machining: Cut a round ingot from the magnesium-lithium alloy ingot obtained in Step 1 by wire cutting, and then remove the surface cutting marks and oxide skin by precision machining on a lathe;
[0009] Step 3, Hot extrusion: Preheat and keep warm the round ingot after precision machining in Step 2, and then perform hot extrusion processing with a large extrusion ratio to obtain a preform;
[0010] Step 4, Tube spinning forging: Put the preform obtained in Step 3 into the lining tube, and then perform spinning forging processing. After peeling off the lining tube, a high-strength, tough and ultrafine-grained magnesium-lithium alloy rod is obtained; the tensile strength of the high-strength, tough and ultrafine-grained magnesium-lithium alloy rod is not less than 330 MPa, and the elongation is not less than 20%.
[0011] The preparation method of the above-mentioned high-strength, tough and ultrafine-grained magnesium-lithium alloy rod is characterized in that in Step 1, when the vacuum degree is 3×10 -2 Pa to 6×10 -2 Pa, turn off the vacuum system. The temperature of heating up and keeping warm for melting, heating up for melting, and heating up and keeping warm is 400°C to 800°C, and the holding time after each heating up is 2 min to 10 min. By strictly controlling the vacuum degree, melting temperature and time before vacuum induction melting, the volatilization of the molten metal is reduced while ensuring its fluidity, thereby reducing the burning loss of raw materials during the melting process.
[0012] The preparation method of the above-mentioned high-strength, tough and ultrafine-grained magnesium-lithium alloy rod is characterized in that the diameter of the round ingot in Step 2 is not less than 30 mm. By machining, a round ingot with appropriate size is selected to match the parameters of subsequent hot extrusion processing, improve the surface quality of the round ingot, reduce the friction resistance during hot extrusion deformation, and facilitate the subsequent deformation processing.
[0013] The preparation method of the above-mentioned high-strength and high-toughness ultrafine-grained magnesium-lithium alloy bar is characterized in that, in step three, the temperatures of the preheating treatment and the hot extrusion processing are both 200°C to 400°C, the heat preservation time of the preheating treatment is 30 min to 60 min, the extrusion ratio of the hot extrusion processing is 16 to 50, and the extrusion speed is 3 mm / s to 5 mm / s. The present invention adopts a relatively high hot extrusion deformation temperature and a large extrusion ratio to improve the surface quality of the bar, promote dynamic recrystallization at the same time, enhance the deformation ability of the material, and ensure that the magnesium-lithium alloy bar obtained by subsequent rotary forging has balanced strength and toughness.
[0014] The preparation method of the above-mentioned high-strength and high-toughness ultrafine-grained magnesium-lithium alloy bar is characterized in that, in step four, the lining tube is a copper tube, and the inner diameter of the copper tube is 0.5 mm larger than the outer diameter of the preform, and the single-pass radial compression amount of the rotary forging processing is 1 mm; the diameter of the high-strength and high-toughness ultrafine-grained magnesium-lithium alloy bar is 6 mm to 8.5 mm. The present invention uses a copper tube as the lining tube, changes the stress state during the material deformation process, reduces the bar defects, guides the magnesium-lithium alloy material to flow along a specific direction at the same time, and improves the preparation efficiency and the dimensional accuracy of the magnesium-lithium alloy bar.
[0015] Meanwhile, the present invention also discloses a high-strength and high-toughness ultrafine-grained magnesium-lithium alloy bar prepared by the above method.
[0016] The present invention has the following advantages compared with the prior art:
[0017] 1. The present invention realizes the uniform distribution of ultrafine grains in the magnesium-lithium alloy bar through the vacuum melting-casting - hot extrusion - lining tube rotary forging process. Compared with the magnesium-lithium alloy bar prepared by the traditional process, its grain size is smaller and the distribution is more uniform, which helps to improve the strength and toughness of the magnesium-lithium alloy bar, gives full play to the performance advantages of the magnesium-lithium alloy. At the same time, the preparation process of the present invention is simple, the process flow is short, and the loss is low, greatly reducing the intermediate links and material loss, improving the production efficiency and material utilization rate, and reducing the production cost.
[0018] 2. The present invention precisely controls the process parameters of each preparation link, including the vacuum degree, melting temperature, heat preservation time, extrusion ratio, pressurization speed, radial compression amount of rotary forging, etc., and precisely regulates the structure and performance of the magnesium-lithium alloy bar, ensuring the stability of the quality of the magnesium-lithium alloy bar.
[0019] 3. The present invention introduces the β-Li phase into the low-lithium magnesium-lithium alloy through composition design, and combines the liner swaging process to improve the workability of the magnesium-lithium alloy, solve the problem of insufficient forming ability of the low-lithium magnesium-lithium alloy, and the prepared magnesium-lithium alloy bar has a smooth and flat surface without obvious defects, reducing the subsequent processing amount and surface treatment difficulty. At the same time, the ultrafine grains are evenly distributed, and the strength and toughness are balanced, improving the overall performance and service life of the product, and better meeting the application scenarios with higher surface quality requirements, especially suitable for preparing lightweight and high-performance complex structural parts and wires required for arc additive manufacturing.
[0020] 4. The preparation method of the present invention synergistically improves the strength and toughness of the magnesium-lithium alloy bar, its tensile strength is not less than 330 MPa, and the elongation is not less than 20%, realizing the matching of strength and toughness.
[0021] The technical solution of the present invention will be further described in detail below with reference to the drawings and embodiments. Brief Description of the Drawings
[0022] Figure 1 It is a scanning diagram of the Mg-5.0Li-6.2Zn-1.69Y alloy ingot prepared in Example 1 of the present invention.
[0023] Figure 2 It is an EBSD diagram of the preform prepared in Example 1 of the present invention.
[0024] Figure 3 It is a macroscopic fracture diagram of the high-strength and high-toughness ultrafine-grained Mg-5.0Li-6.2Zn-1.69Y alloy bar prepared in Example 1 of the present invention. Detailed Description of the Embodiments
[0025] Example 1
[0026] The high-strength and high-toughness ultrafine-grained magnesium-lithium alloy bar of this example is composed of the following components by mass percentage: Li 5.0%, Zn 6.2%, Y 1.69%, and the rest is magnesium and unavoidable impurities:
[0027] The preparation method of the high-strength and high-toughness ultrafine-grained magnesium-lithium alloy bar of this example includes the following steps:
[0028] Step 1. Vacuum induction melting: Put magnesium ingots and lithium ingots into the vacuum induction melting furnace and close the furnace door. Turn on the circulating water and vacuum system of the vacuum induction melting furnace in sequence. Wait until the vacuum degree is 3×10 -2When the pressure reaches Pa, the vacuum system is closed and argon gas is introduced into the furnace. First, the temperature is raised to 400 °C and held for 5 minutes, then the temperature is raised to 630 °C and held for 8 minutes. During this period, observe the melting situation of the metal ingot at all times. After the magnesium ingot and lithium ingot are completely melted, zinc granules and magnesium-yttrium master alloy are gradually added through a feeder. The temperature is raised to 700 °C and held for 10 minutes for smelting. At the same time, turn on the mechanical stirring system and stir at a fixed speed until the metal liquid is evenly mixed. Stop stirring and raise the temperature to 750 °C and hold for 2 minutes, then pour the metal liquid into a cast iron mold with a diameter of 60 mm and a length of 200 mm. After cooling and forming, a Mg-5.0Li-6.2Zn-1.69Y alloy ingot is obtained;
[0029] Step 2. Machining: Cut a round ingot with a diameter of 50 mm from the Mg-5.0Li-6.2Zn-1.69Y alloy ingot obtained in Step 1 by wire cutting, and then remove the surface cutting marks and oxide scales by precision machining on a lathe;
[0030] Step 3. Hot extrusion: Put the round ingot after precision machining in Step 2 into a box-type resistance furnace, raise the temperature to 350 °C and hold for 30 minutes for preheating treatment. Then select a mold with a diameter of 12.5 mm and place it in an extruder for hot extrusion processing. The hot extrusion temperature is 350 °C, the extrusion ratio is 16, the extrusion speed is 3 mm / s, and it is air-cooled to room temperature to obtain a preform;
[0031] Step 4. Tube lining swaging: Put the preform obtained in Step 3 into a copper tube. The inner diameter of the copper tube is 0.5 mm larger than the outer diameter of the preform. Then, at room temperature, perform 4-pass swaging processing with a single-pass radial compression amount of 1 mm. After peeling off the copper tube, a high-strength and tough ultrafine-grained Mg-5.0Li-6.2Zn-1.69Y alloy bar with a diameter of 8.5 mm is obtained.
[0032] After testing, the yield strength and tensile strength of the high-strength and tough ultrafine-grained Mg-5.0Li-6.2Zn-1.69Y alloy bar prepared in this example are 278 MPa and 332 MPa respectively, and the elongation is 24.5%. Its average grain size and density are 0.98 μm and 1.65 g / cm 3 .
[0033] Figure 1 is the scanning diagram of the Mg-5.0Li-6.2Zn-1.69Y alloy ingot prepared in this example. From Figure 1 it can be seen that after adding Zn and Y, brown β-Li phase, skeletal W phase and massive MgZn 2 phase are present along the grain boundaries in the magnesium-lithium alloy.
[0034] Figure 2 is the EBSD diagram of the preform prepared in this example. From Figure 2It can be seen that after hot extrusion deformation, except for a small number of deformed grains, the extruded Mg-5.0Li-6.2Zn-1.69Y alloy is mainly composed of fine recrystallized grains, indicating that hot extrusion processing promotes the occurrence of dynamic recrystallization, and the grains are significantly refined. After statistics, the grain size is about 2 μm.
[0035] Figure 3 This is the macroscopic fracture surface diagram of the high-strength and tough ultrafine-grained Mg-5.0Li-6.2Zn-1.69Y alloy bar prepared in this example. From Figure 3 It can be seen that this fracture surface is mainly composed of uniform and fine dimples, indicating that the fracture mode of this alloy is ductile fracture.
[0036] Example 2
[0037] The high-strength and tough ultrafine-grained magnesium-lithium alloy bar of this example is composed of the following components by mass percentage: Li 4.5%, Zn 7.3%, Y 1.5%, and the rest is magnesium and inevitable impurities:
[0038] The preparation method of the high-strength and tough ultrafine-grained magnesium-lithium alloy bar of this example includes the following steps:
[0039] Step 1. Vacuum induction melting: Put magnesium ingots and lithium ingots into a vacuum induction melting furnace and close the furnace door. Turn on the circulating water and vacuum system of the vacuum induction melting furnace in sequence. When the vacuum degree reaches 6×10 -2 Pa, close the vacuum system and introduce argon into the furnace. First, heat up to 400 °C and keep it warm for 5 min, then heat up to 650 °C and keep it warm for 10 min. Observe the melting situation of the metal ingots at all times. After the magnesium ingots and lithium ingots are completely melted, gradually add zinc grains and magnesium-yttrium master alloy through a feeder, heat up to 750 °C and keep it warm for 8 min for melting. At the same time, turn on the mechanical stirring system to stir at a fixed speed until the molten metal is evenly mixed. Stop stirring and heat up to 800 °C and keep it warm for 3 min, then pour the molten metal into a cast iron mold with a diameter of 60 mm and a length of 200 mm. After cooling and forming, obtain a Mg-4.5Li-7.3Zn-1.5Y alloy ingot;
[0040] Step 2. Machining: Use wire cutting to cut a round ingot with a diameter of 50 mm from the Mg-4.5Li-7.3Zn-1.5Y alloy ingot obtained in Step 1, and then use a lathe for finish machining to remove surface cutting marks and oxide scales;
[0041] Step 3. Hot extrusion: Put the round ingot after finish machining in Step 2 into a box-type resistance furnace, heat up to 200 °C and keep it warm for 45 min for preheating treatment, then select a mold with a diameter of 10 mm, place it in an extruder for hot extrusion processing. The hot extrusion temperature is 300 °C, the extrusion ratio is 25, the extrusion speed is 5 mm / s, and air-cool to room temperature to obtain a preform;
[0042] Step 4. Tube spinning forging: The preform obtained in Step 3 is sleeved into a copper tube. The inner diameter of the copper tube is 0.5 mm larger than the outer diameter of the preform. Then, at room temperature, spinning forging is carried out in 3 passes with a single-pass radial compression of 1 mm. After peeling off the copper tube, a high-strength, tough and ultrafine-grained Mg-4.5Li-7.3Zn-1.5Y alloy rod with a diameter of 7 mm is obtained.
[0043] After testing, the yield strength and tensile strength of the high-strength, tough and ultrafine-grained Mg-4.5Li-7.3Zn-1.5Y alloy rod prepared in this example are 279 MPa and 342 MPa respectively, and the elongation is 23%. Its average grain size and density are 0.87 μm and 1.67 g / cm 3 .
[0044] Example 3
[0045] The high-strength, tough and ultrafine-grained magnesium-lithium alloy rod of this example is composed of the following components by mass percentage: Li 2.0%, Zn 7.8%, Y 3.5%, and the rest is magnesium and inevitable impurities:
[0046] The preparation method of the high-strength, tough and ultrafine-grained magnesium-lithium alloy rod of this example includes the following steps:
[0047] Step 1. Vacuum induction melting: Put magnesium ingots and lithium ingots into a vacuum induction melting furnace and close the furnace door. Turn on the circulating water and vacuum system of the vacuum induction melting furnace in sequence. When the vacuum degree reaches 5×10 -2 Pa, close the vacuum system and introduce argon into the furnace. First, heat up to 400 °C and keep it warm for 5 min, then heat up to 630 °C and keep it warm for 8 min. During this period, observe the melting situation of the metal ingots at all times. After the magnesium ingots and lithium ingots are completely melted, gradually add zinc granules and magnesium-yttrium master alloy through a feeder, heat up to 720 °C and keep it warm for 10 min for melting. At the same time, turn on the mechanical stirring system to stir at a fixed speed to obtain a uniformly mixed metal liquid. Stop stirring and heat up to 750 °C and keep it warm for 1 min, then pour the metal liquid into a cast iron mold with a diameter of 60 mm and a length of 200 mm. After cooling and forming, a Mg-2.0Li-7.8Zn-3.5Y alloy ingot is obtained;
[0048] Step 2. Machining: Use wire cutting to cut a round ingot with a diameter of 49 mm from the Mg-2.0Li-7.8Zn-3.5Y alloy ingot obtained in Step 1, and then use a lathe for finish machining to remove the surface cutting marks and oxide scales;
[0049] Step 3. Hot extrusion: The precision-machined ingot in Step 2 is placed in a box-type resistance furnace and heated to 400 °C for preheating treatment for 60 min. Then, a die with a diameter of 7 mm is selected and placed in an extruder for hot extrusion processing. The hot extrusion temperature is 250 °C, the extrusion ratio is 50, the extrusion speed is 3 mm / s, and it is air-cooled to room temperature to obtain a preform;
[0050] Step 4. Tube lining rotary forging: The preform obtained in Step 3 is sleeved into a copper tube with an inner diameter 0.5 mm larger than the outer diameter of the preform. Then, rotary forging processing with a single-pass radial compression amount of 1 mm in 1 pass is carried out at room temperature. After peeling off the copper tube, a high-strength, tough and ultrafine-grained Mg-2.0Li-7.8Zn-3.5Y alloy bar with a diameter of 6 mm is obtained.
[0051] After testing, the yield strength and tensile strength of the high-strength, tough and ultrafine-grained Mg-2.0Li-7.8Zn-3.5Y alloy bar prepared in this example are 269 MPa and 330 MPa respectively, and the elongation is 20%. Its average grain size and density are 1 μm and 1.64 g / cm 3 .
[0052] The above is only a preferred embodiment of the present invention and does not impose any limitation on the present invention. Any simple modification, change and equivalent change made to the above embodiments according to the technical essence of the invention still fall within the protection scope of the technical solution of the present invention.
Claims
1. A method for preparing a high-strength and high-toughness ultrafine-grained magnesium-lithium alloy rod, characterized in that: The magnesium-lithium alloy rod is composed of the following components in mass percentage: Li 2% to 5%, Zn 6% to 8%, Y 1.5% to 3.5%, and the rest is magnesium and inevitable impurities. The preparation method comprises the following steps: Step 1: Vacuum induction melting: Turn on the circulating water and vacuum system of the vacuum induction melting furnace and wait until the vacuum degree is lower than 6×10 -2 When the temperature reaches 0.045°C, the vacuum system is turned off and argon gas is introduced into the furnace. The temperature is increased and maintained for melting respectively, so that the magnesium ingot and the lithium ingot are completely melted. Then, zinc particles and magnesium-yttrium intermediate alloy are gradually added through the feeder. The mechanical stirring system is turned on to stir at a fixed speed. At the same time, the temperature is increased for melting to obtain molten metal. After further increasing the temperature and maintaining the temperature, the molten metal is poured into a mold, and after cooling, a magnesium-lithium alloy ingot is obtained. Step 2, mechanical processing: using wire cutting to cut a round ingot from the magnesium-lithium alloy ingot obtained in step 1, and then using a lathe to finish-process to remove surface cuts and oxide scale; Step 3, hot extrusion: preheating the round ingot after fine processing in step 2 and keeping it warm, and then performing high extrusion heat extrusion processing to obtain a prefabricated billet; Step 4, rotary forging of the liner: insert the prefabricated blank obtained in step 3 into the liner, and then perform rotary forging. After stripping the liner, a high-strength and tough ultrafine-grained magnesium-lithium alloy rod is obtained; the tensile strength of the high-strength and tough ultrafine-grained magnesium-lithium alloy rod is not less than 330MPa, and the elongation is not less than 20%.
2. The method for preparing a high-strength and tough ultrafine-grained magnesium-lithium alloy rod according to claim 1, characterized in that: In step 1, wait until the vacuum degree reaches 3×10 -2 Pa~6×10 -2 The vacuum system is closed at Pa, the temperatures of the heating and heat preservation melting and the heating melting and heating preservation are both 400° C. to 800° C., and the insulation time after each heating is 2 min to 10 min.
3. The method for preparing a high-strength and tough ultrafine-grained magnesium-lithium alloy rod according to claim 1, characterized in that: The diameter of the round ingot in step 2 is not less than 30 mm.
4. The method for preparing a high-strength and tough ultrafine-grained magnesium-lithium alloy rod according to claim 1, characterized in that: The temperatures of the preheating treatment and hot extrusion processing in step three are both 200° C. to 400° C., the holding time of the preheating treatment is 30 min to 60 min, the extrusion ratio of the hot extrusion processing is 16 to 50, and the extrusion speed is 3 mm / s to 5 mm / s.
5. The method for preparing a high-strength and tough ultrafine-grained magnesium-lithium alloy rod according to claim 1, characterized in that: The liner tube in step 4 is a copper tube, and the inner diameter of the copper tube is 0.5 mm larger than the outer diameter of the prefabricated blank. The radial compression of the single-pass rotary forging process is 1 mm; the diameter of the high-strength and tough ultrafine-grained magnesium-lithium alloy rod is 6 mm to 8.5 mm.
6. A high-strength and tough ultrafine-grained magnesium-lithium alloy rod prepared by the method described in any one of claims 1 to 5.